2008
DOI: 10.1038/emboj.2008.239
|View full text |Cite
|
Sign up to set email alerts
|

Silencing and transcriptional properties of the imprinted Airn ncRNA are independent of the endogenous promoter

Abstract: The Airn macro ncRNA is the master regulator of imprinted expression in the Igf2r imprinted gene cluster where it silences three flanking genes in cis. Airn transcription shows unusual features normally viewed as promoter specific, such as impaired post-transcriptional processing and a macro size. The Airn transcript is 108 kb long, predominantly unspliced and nuclear localized, with only a minority being variably spliced and exported. Here, we show by deletion of the Airn ncRNA promoter and replacement with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…We previously reported a tetracycline (Tet)-inducible Airn allele (Stricker et al, 2008). However, owing to gain of Tet-Airn DNA methylation, these cells were not suitable for further experiments (supplementary material Fig.…”
Section: Two Inducible Systems To Control the Airn Lncrnamentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported a tetracycline (Tet)-inducible Airn allele (Stricker et al, 2008). However, owing to gain of Tet-Airn DNA methylation, these cells were not suitable for further experiments (supplementary material Fig.…”
Section: Two Inducible Systems To Control the Airn Lncrnamentioning
confidence: 99%
“…We initially attempted to control endogenous Airn expression using a TetOn system (Stricker et al, 2008). However, the Tetdriven Airn promoter was modified by DNA methylation and the effects of inducing Airn expression could be assayed only in a subset of cells.…”
Section: Inducible Esc Systems To Control Endogenous Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Airn macro ncRNA is the master regulator of imprinted expression in the Igf2 receptor ( Igfr ) imprinted gene cluster, where it silences 3 flanking genes in cis [Stricker et al, 2008]. Airn expression not only induces silencing of flanking mRNA genes but also protects the paternal copy of ICE from de novo methylation.…”
Section: Gnrha Treatment Affects Lncrnasmentioning
confidence: 99%
“…74 However, replacement of the Airn promoter with the mouse Pgk1 promoter showed that the endogenous promoter does not control the low splicing capacity of the Airn lncRNA. 75 Both the Airn and Kcnq1ot1 macro lncRNAs are unusual in that their CpG island lies immediately downstream of the promoter and although they lack sequence similarities, they each contain a series of tandem direct repeats that have been suggested to guide epigenetic modifications such as the acquisition of the maternal-specific methylation imprint. 76 In support of this, the Airn tandem direct repeats have recently been shown to be necessary for the oocyte-specific DNA methylation imprint.…”
Section: The Unusual Transcript Biology Of Macro Lncrnasmentioning
confidence: 99%